Recent Development of Heterocyclic Compounds with Indazole Moiety as Potential Antiparasitic Agents - Paul, Abhik; Guria, Tanmoy; Roy, Puspita; Maity, Arindam (Current Topics in Medicinal Chemistry, 2022)
Indazole is a vital nitrogen-containing heterocyclic unit in organic and medicinal chemistry research and a helpful precursor molecule for the production of various types of encirclement heterocycles. Indazole analogues are diverse pharmacological agents that can be used to treat a variety of conditions, including cancer, inflammation, infectious diseases, and neurological problems. In fact, the indazole moiety containing inhibitors also showed excellent medicinal properties for the treatment of parasitic diseases. Therefore, the development of new inhibitors has immense promise for usage as key components for the next generation of antiparasitic medication. In this review, we have summarized the recent developments of indazole-containing antiparasitic inhibitors, specially anti-protozoal, anti-fungal, and antiamoebic inhibitors, as well as their structure-activity relationship (SAR) findings for medicinal chemists who are searching for new preclinical parasitic drug candidates.
Keywords: Structure activity relationship (SAR)